Cardiometabolic risk pathways in adults with disabilities: A structural equation model of diet quality and functional ability - Radwan Qasrawi; Suliman Thwaib; Ghada Issa; Rand Al Taweel; Razan Abu Ghoush; Malak Amro; Hazem Agha; Diala Abu Al-Halawa; Haneen Al Taweel; Raghad Amro; Ayoub Jawaldeh (PLoS ONE, 2026)
Background Adults with disabilities experience increased cardiometabolic risk, yet the pathways linking nutrition, functional ability, and environmental factors remain insufficiently defined. This study examined these relationships using a structural equation modeling framework. Methods A cross-sectional study was conducted among 123 adults with disabilities in Palestine (mean age 31.9 years). Data included anthropometric measures, two non‑consecutive 24-hour dietary recalls, disability severity (Disability Rating Scale), functional ability (Barthel Index), psychosocial environment, and socioeconomic indicators. Dietary quality and adequacy were assessed using the Diet Quality Index (DQI) and Mean Adequacy Ratio (MAR). Seven latent constructs were specified and tested using confirmatory factor analysis and structural equation modeling. Results Indicators of cardiometabolic risk were prevalent: 58.5% overweight/obese and 51.2% had inadequate intake. Disability severity correlated with reduced muscle mass and poorer diet quality. Nutritional adequacy positively predicted body composition (β = 0.274) and functional ability (β = 0.185). Functional ability and physical activity were inversely associated with adiposity, while sedentary behavior moderated the relationship between diet quality and waist circumference. Mental illness specifically impaired diet quality, but not caloric intake. Urban residence and lower education predicted poorer dietary outcomes. The model explained 63.7% of variance in body composition and 94.4% in functional ability. Conclusions Cardiometabolic risk in adults with disabilities is shaped by interrelated pathways involving disability severity, nutrition, functional capacity, and psychosocial factors. Lower anthropometric measures may reflect muscle loss rather than reduced risk. Interventions should focus on improving nutritional adequacy, supporting functional independence, addressing mental health, and reducing environmental barriers.